Fine-tuning of mast cell activation by FceRIbeta chain - Ra, Chisei; Nunomura, Satoshi; Okayama, Yoshimichi (Frontiers in Immunology, 2012)
Mast cells play the key role in allergic reaction and disorders, being activated by the high affinity receptor for IgE, FceRI. There are two types of FceRI expressed on the cell surface of human mast cells, abg2 type and ag2　type (without b chain), while in mouse mast cells only the tetrameric abg2 type is expressed. In the lesion of allergic inflammation such as atopic conjunctivitis and atopic dermatitis, mast cells increase in number and exclusively express the abg2 type FceRI, in contrast in healthy conjunctiva and skin most mast cells express the ag2　type. The human and mouse FceRI genes contain seven exons and in the human gene we found a repressor element locates in the forth intron. Through the repressor element HDACs are recruited to the FceRIb gene by MZF-1/FHL3/NFY complex and repress b transcription by deacetylation of histones in the presence of GM-CSF. It has been long recognized that the function of the b chain ITAM is a signal amplifier, but we have recently revealed bidirectional (positive and negative) functions of the b chain ITAM in the regulation of the mast cell activation and effector functions. Namely, the b chain enhances the mast cell activation signal triggered with low intensity stimulation such as lower dose antigen than threshold while it suppresses the signal of high intensity stimulation. Employing mouse model of CHS induced by oxazolone, we have revealed that IgE-mediated mast cell activation is required for CHS and that the b chain is crucially involved in this model. On the other hand diverse immune receptors including TLRs, SCF receptor and GPCRs are known to mediate signals which modulate FceRI・adenosine receptors, one of GPCRs, trigger synergistic degranulation response in mast cells even when the FceRI stimulation is of ‘lower intensity’ than the threshold. We have recently elucidated, in this synergistic degranulation response, b chain ITAM plays positive role, possibly reflecting in vivo allergic response.